Analisis Faktor Eksternal dan Pemasaran pada Bisnis Swipewash Marketplace untuk Layanan Laundry - Indah Erlinda Ade Kisworo; Dimas Angga Negoro; Kustiawan, Unggul; Abadi, Ferryal (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The e-commerce industry in Indonesia is experiencing rapid growth, supported by a large population, a growing middle class, and increasing internet penetration. In a busy urban society, these services are becoming an essential need. Digital platforms can provide solutions with easy access, transparency, and efficiency for consumers. SwipeWash offers an e-commerce platform for laundry, bag spa, and shoe spa services equipped with superior features. The EFE (External Factor Evaluation) Matrix analysis produced a score of 3.15. This score indicates that SwipeWash has responded well to external factors. Some of the main opportunities identified include the growth in the adoption of mobile technology and e-commerce with a weight of 0.80, an increase in digital payment users with a weight of 0.60, and automation of the laundry process to increase efficiency with a weight of 0.45. Other factors that support SwipeWash's competitiveness are close relationships with laundry partners and a structured marketing strategy. To build a sustainable competitive advantage, SwipeWash applies VRIO analysis which helps companies identify internal aspects that have high strategic value.